Anatomical Description of a Variant Abductor Digiti Minimi Accessorious Muscle and Its Clinical Correlation with Ulnar Neurovascular Entrapment Syndrome. - Avinash T; Smita T; Mona S; Vandana M; Rajesh KS; Gayatri R (Department of Surgery, UKM Medical Centre, 2014)
Variations of the abductor digiti minimi muscle are a rare occurrence as compared to anomalous thenar musculature. Surgico-anatomical basis of such accessory muscular slips should be discussed in detail. This case report presents a rare bilateral existence of accessory slips of abductor digiti minimi originating from the antebrachial fascia and flexor retinaculum in a male cadaver. Hypertrophy of these muscular heads can be occult etiologies in causation of ulnar entrapment neuropathies. Such anomalous muscles can prove to be a boon or bane for an operating surgeon. On one hand, they can be the guiding factor in planning myofascial flaps and on the other; they can cause unwanted iatrogenic complications during antero-medial approach through the wrist tendons. Nevertheless, the presence of accessory bellies in the hypothenar eminence deserve a special mention especially if present bilaterally. The authors have attempted to assign an embryological explanation for the above anomaly and have discussed its possible link with various clinical syndromes.